2017
DOI: 10.1038/pj.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale monolayer adsorption of polyelectrolytes at the solid/liquid interface observed by quartz crystal microbalance

Abstract: As a device with excellent potential, the quartz crystal microbalance (QCM) has been developed to study the interfacial properties of liquids, such as adsorption/desorption kinetics, electrochemical reaction mechanisms and interfacial viscosity. In this research, the adsorption properties of cationic polyelectrolytes (poly(diallyl dimethylammonium chloride) and poly(allylamine hydrochloride)) on solid surfaces were observed using QCM. The results indicated that the response to adsorption was different with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…It is obvious that a frequency shift on the silica surface is higher than that on the calcite surface, suggesting that the mass adsorbed rapidly on the surface [15]. These results are in line with those of Guo et al [20], who noted that a higher shift in the frequency was on the silica surface than that on the gold surface. They stated that silica (SiO2) has higher electrostatic contact sites compared to the other surfaces, leading to more molecules adsorbed on the SiO2 surface through the electrostatic attraction.…”
Section: Adsorption Of Crude Oil On Calcite and Silica Surfacessupporting
confidence: 91%
See 1 more Smart Citation
“…It is obvious that a frequency shift on the silica surface is higher than that on the calcite surface, suggesting that the mass adsorbed rapidly on the surface [15]. These results are in line with those of Guo et al [20], who noted that a higher shift in the frequency was on the silica surface than that on the gold surface. They stated that silica (SiO2) has higher electrostatic contact sites compared to the other surfaces, leading to more molecules adsorbed on the SiO2 surface through the electrostatic attraction.…”
Section: Adsorption Of Crude Oil On Calcite and Silica Surfacessupporting
confidence: 91%
“…8,11,13,35 A quartz crystal microbalance (QCM) has been extensively used to detect the adsorption and interactions of polymers at solid/liquid interfaces. For instance, Guo and colleagues 20 investigated the adsorption behavior of two cationic polyelectrolytes that have different charge densities on silica and gold surfaces. The results revealed that the adsorption of the polyelectrolyte relies on the solid surface, solution concentration, and solution pH.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the peculiar physical properties of polymer chains in close proximity to inorganic solid interfaces have been extensively studied. The thermal mobility of chains at the solid interface has been shown to be extremely depressed, with respect to that in the bulk, because of the confinement effect. Also, chains are irreversibly adsorbed onto the surface of the inorganic solids and thereby cannot be removed, even after washing in a good solvent. This is now recognized as an irreversibly adsorbed insoluble layer. Several groups have hitherto reported that the adsorbed layer grows via thermal annealing at a temperature above the glass-transition temperature ( T g ). , …”
mentioning
confidence: 99%
“…A QCM is essentially a balance that could be used to precisely measure ultrasmall masses in real-time, allowing the user to closely follow extremely subtle changes. Over the last few decades, QCMs have been used in a growing number of technologies and research applications, such as surface interaction processes monitors, piezoelectric immunosensors, nanoscale characterization tools, and various specific molecule sensors. …”
mentioning
confidence: 99%